A kind of fluororubber primer-free coating resistant to freezing liquid, preparation method and application thereof

By using refrigerant-resistant fluoro-rubber primer-free coating, using specific A and B ingredients and preparation methods, the existing fluoro-rubber primer is solved, and the good refrigerant resistance and high production efficiency of the fluoro-rubber composite board is achieved.

CN118685115BActive Publication Date: 2025-03-18GUILIN JINGU NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410878429.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2025-03-18
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

The existing fluoroelastic primer is prone to hydrolysis when in contact with the refrigerant, resulting in poor product stability of the cylinder gasket material, cumbersome coating process and low production efficiency.

Method used

A fluoro-rubber primer coating that is resistant to freezing liquid is used, which is mixed with material A and material B in a volume ratio of 5:0.8-1.2. Material A includes fluoro-rubber, activated magnesium oxide, carbon black, graphite and adhesive additives. Material B includes accelerator, composite vulcanizing agent and solvent. Through specific preparation methods and composition ratios, the adhesion of the paint and the refrigerant resistance performance are improved.

Benefits of technology

The good bond between the fluoroelastic coating and the metal plate is achieved, and the obtained fluoroelastic composite plate has good refrigeration resistance, compression resistance and heat resistance, simplifying the coating process and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118685115B_ABST
    Figure CN118685115B_ABST
Patent Text Reader

Abstract

The invention discloses a fluororubber primer-free coating resistant to freezing liquid, a preparation method and an application thereof, wherein the fluororubber primer-free coating is composed of material A and material B, wherein the raw materials of material A include 40-60 parts of fluororubber, 5-8 parts of active magnesium oxide, 5-10 parts of carbon black, 5-10 parts of graphite, 2-4 parts of bonding aid and 100-200 parts of solvent; and the raw materials of material B include 1-1.5 parts of accelerator, 1.5-3 parts of composite vulcanizing agent and 40-100 parts of solvent. The viscosity of the fluororubber primer-free coating resistant to freezing liquid obtained by the method of the invention is 2500-3500 mPa·S, and the metal fluororubber composite plate prepared by using the coating without primer is immersed in a freezing liquid mixed with ethylene glycol and water in a ratio of 1:1 for more than 500 hours without bubbling or falling off, and has excellent resistance to automobile freezing liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical coatings, and in particular to a fluororubber primer-free coating resistant to freezing liquid, a preparation method and application thereof. Background Art

[0002] Metal fluororubber composite plate is a metal plate with fluororubber obtained by coating the metal surface with fluororubber coating. It is widely used in high-end rubber cars, trucks, motorcycles and other internal combustion engine cylinder gasket materials with high requirements. The raw materials for preparing metal fluororubber composite plate mainly include fluororubber, fluororubber primer and metal plate.

[0003] Fluororubber primer is a special adhesive for bonding fluororubber to metal plates, and its main component is generally silane coupling agent resin. For example, Chemlok 607 adhesive produced by LORD Corporation, which is commonly used in the market, is a silane-based special adhesive specially used for bonding silicone rubber, fluororubber and metal to prepare metal fluororubber composite plates. When the internal combustion engine cylinder made of the metal fluororubber composite plate is in contact with the refrigerant for a long time, the silicon atoms of the silane coupling agent resin and the hydroxide ions of the water molecules form silicon-oxygen bonds, causing the silane coupling agent resin structure to change, so that the bonding between the fluororubber coating and the metal substrate surface is destroyed, and then the product stability of the cylinder gasket material is poor and the quality is difficult to guarantee.

[0004] In order to solve the problem of poor product stability caused by the reaction between silicon atoms of the special adhesive in the cylinder gasket material and the hydroxide ions of water in the refrigerant, the prior art CN102756528B discloses a method for preparing a metal fluororubber composite plate. The fluororubber primer in the preparation method does not use silane substances. The fluororubber primer consists of 100 parts by weight of 26 type fluororubber raw rubber, 1-6 parts by weight of fumed silica, 15-40 parts by weight of carbon black, 2-15 parts by weight of active magnesium oxide, 0-10 parts by weight of calcium hydroxide and 0.4-2.0 parts by weight of zinc stearate. After being uniformly mixed on an open mill / internal mixer, a mixed solvent of 2-4 times the weight of the mixed rubber is added, and the mixture is fully dissolved and filtered to obtain a composite plate. When used, 2-6 parts by weight of a bisphenol AF composite vulcanizing agent is added. The fluororubber primer in the invention needs to be used together with an adhesion promoter, that is, the fluororubber primer cannot be directly coated on the surface of the cleaned metal substrate, but the adhesion promoter must be coated on the surface of the metal substrate first, and then the fluororubber primer with bisphenol AF composite vulcanizer added is coated. The coating process is cumbersome and the production efficiency of the metal fluororubber composite plate is low.

[0005] In order to solve the problem of poor product stability caused by the easy hydrolysis of the fluororubber primer containing silane coupling agents, and to overcome the defects of complicated coating process and low production efficiency, it is urgently necessary to prepare a fluororubber primer-free coating with excellent resistance to freezing liquid for the preparation of automobile internal combustion engine cylinder gasket materials.

[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0007] The purpose of the present invention is to provide a fluororubber primer-free coating resistant to freezing liquid, aiming to solve the problem of poor stability of cylinder gasket products caused by easy hydrolysis of fluororubber primer containing silane coupling agent, and to overcome the defects of complicated coating process and low production efficiency.

[0008] Another object of the present invention is to provide a method for preparing a fluororubber primer-free coating resistant to freezing liquid, aiming to obtain a fluororubber coating with increased adhesion and significantly improved freezing liquid resistance while keeping other properties unchanged or even improved.

[0009] To achieve the above-mentioned purpose, the present invention provides a fluororubber primer-free coating resistant to freezing liquid, wherein the fluororubber primer-free coating is composed of material A and material B in a volume ratio of 5:0.8-1.2, wherein the raw materials of material A include 40-60 parts of fluororubber, 5-8 parts of active magnesium oxide, 5-10 parts of carbon black, 5-10 parts of graphite, 2-4 parts of an adhesive aid and 100-200 parts of a solvent; and the raw materials of material B include 1-1.5 parts of an accelerator, 1.5-3 parts of a composite vulcanizing agent and 40-100 parts of a solvent.

[0010] Preferably, in the above technical solution, the composite vulcanizing agent includes one or both of triazine trithiol compounds and bisphenol AF.

[0011] Preferably, in the above technical solution, the accelerator is benzyltriphenylphosphonium chloride, and the adhesion promoter is an amino compound.

[0012] Preferably, in the above technical solution, the active magnesium oxide is composed of four particle sizes of active magnesium oxide. In terms of weight percentage, the proportions of the four particle sizes of active magnesium oxide are as follows: the content of particle size ≤100nm is 5-15%, the content of 100nm<particle size≤200nm is 60-70%, the content of 200nm<particle size≤250nm is 15-25%, and the content of 250nm<particle size is 4-10%.

[0013] According to the above technical scheme, the present invention adopts a specific preparation method to prepare four kinds of activated magnesium oxide with different particle sizes, and the activated magnesium oxide with different particle sizes is combined with carbon black with a larger particle size to avoid rough paint surface after coating; at the same time, the active magnesium oxide of the present invention has the characteristics of high activity and large surface area, many dangling bonds inside the active magnesium oxide have strong adsorption force on other substances, and the molecules or atoms of the components of A material and B material are cross-linked to improve the viscosity between the A material and the plate, the viscosity between the components of A material, and the viscosity between the surface of A material and the surface of B material; however, the particle size of the active magnesium oxide is small, the surface area is large, the friction between the particles of the active magnesium oxide powder is large, and the fluidity is poor. The addition of graphite improves the fluidity of the active magnesium oxide and carbon black, and promotes the uniform spreading of the A material on the plate during coating.

[0014] Preferably, in the above technical solution, the preparation method includes material preparation, ingredient mixing, material A preparation and material B preparation, and the specific method is as follows:

[0015] S1, preparation: preparing activated magnesium oxide and carbon black;

[0016] S2, ingredients: by weight, take 40-60 parts of fluororubber, 5-8 parts of active magnesium oxide, 5-10 parts of carbon black, 5-10 parts of graphite, 1-1.5 parts of accelerator, 1.5-3 parts of composite vulcanizing agent, 2-4 parts of bonding agent and 200-300 parts of solvent;

[0017] S3, preparation of material A: taking the fluororubber, carbon black, graphite, adhesive additive and a preset amount of solvent into a stirring kettle and mixing them evenly to prepare pre-treated material A, grinding the pre-treated material A, filtering and packaging to prepare material A;

[0018] S4, preparation of material B: taking the accelerator, the composite vulcanizing agent, and a preset amount of solvent and placing them in a stirring kettle, stirring and dissolving and mixing, to obtain material B;

[0019] S5, the material A and the material B are uniformly mixed at a ratio of 5:0.8-1.2 to prepare a fluororubber primer-free coating.

[0020] Preferably, in the above technical solution, in the step S1, the ash content of the carbon black is 0.32-0.47%, and the average particle size is 100 μm.

[0021] Preferably, in the above technical solution, in step S1, the specific steps of preparing the activated magnesium oxide are as follows:

[0022] (1) Preparing a precursor magnesium hydroxide: preparing a solution of magnesium chloride hexahydrate and urea in a preset ratio, heating the water area to precipitate, adding a dispersant to react for 3-6 hours, cooling naturally and aging for 1 hour, filtering, washing, and taking a white precipitate to obtain a precursor magnesium hydroxide;

[0023] (2) Preparation of active magnesium oxide: The precursor magnesium hydroxide is heated in a muffle furnace to 700-750° C. at a heating rate of 6-10° C., kept warm and calcined for 30-50 min, and then cooled to 500-550° C. and kept warm and calcined for 60-90 min to obtain active magnesium oxide, wherein the proportions of the four particle sizes of active magnesium oxide are as follows, by weight percentage: the content of particle size ≤100 nm is 5-15%, the content of 100 nm < particle size ≤200 nm is 60-70%, the content of 200 nm < particle size ≤250 nm is 15-25%, and the content of 250 nm < particle size is 4-10%.

[0024] According to the above technical scheme, the present invention is slowly heated to 700-750℃ for calcination in the early stage to promote the uniform action of polyethylene glycol octylphenyl ether molecules on the precursor magnesium hydroxide, reduce the large-scale aggregation of magnesium hydroxide, and avoid heating too fast at the same time. The aggregated precursor magnesium hydroxide quickly decomposes to release a large amount of gas to form a large solid particle size of magnesium oxide with poor activity. The 700-750℃ heat preservation calcination is set to decompose the precursor magnesium hydroxide to form magnesium oxide with many small holes left inside and on the surface, and then calcine by cooling to 500-550℃, so that the formed magnesium oxide lacks enough kinetic energy to rearrange to form crystals, and the formed magnesium oxide has low crystallinity and unsaturated valence bonds on the surface of magnesium oxide, so it has high activity and high specific surface area. The MnO2 component in the additive has the effect of regulating the decomposition process and improving the properties of magnesium oxide.

[0025] Preferably, in the above technical solution, the additives are 1.4% by mass of polyethylene glycol octylphenyl ether and 0.4% by mass of MnO2.

[0026] An application of a fluororubber primer-free coating resistant to freezing liquid, characterized in that material A and material B in the fluororubber primer-free coating with excellent freezing liquid resistance as described above are mixed evenly at a ratio of 5:0.8-1.2, and then coated on a cleaned metal plate by roller coating, spray coating, flow coating or dip coating, and a composite plate is obtained by high-temperature vulcanization for preparing a cylinder gasket of an internal combustion engine of an automobile.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The principle that the primer-free fluororubber coating prepared by the present invention can achieve good primer-free adhesion to stainless steel, cold-rolled plate and aluminum plate, and the obtained fluororubber composite plate has good resistance to freezing liquid, crushing resistance and heat resistance is as follows: First, the chemical structure of the triazine trithiol compound has a triazine trithiol group such as

[0029]

[0030] As shown, the group contains multiple SH side groups, and the SH groups react with fluororubber and metal under the accelerator and high temperature to form a strong network chemical structure (MXR, M is metal, X is triazine trithiol group, R is rubber) between the fluororubber and the metal, thereby improving the adhesion between the coating and the metal plate. Furthermore, the chemical structure does not undergo hydrolysis reaction with water, and its structure does not change under the temperature condition of 120°C, so that the prepared metal fluororubber composite plate has good water resistance under the temperature condition of 120°C; secondly, a specific method is used to prepare high-activity magnesium oxide containing different particle sizes, the active magnesium oxide has a small particle size and a large friction force, and works with fluororubber to improve the viscosity of the coating components to stainless steel, cold-rolled plate, aluminum plate and other plates; thirdly, graphite improves the fluidity or dispersibility of the components in the coating, promotes the uniform spreading of the coating, and makes the various components of the coating evenly distributed during coating, thereby enhancing the role of each component and improving the bonding effect between the coating and stainless steel, cold-rolled plate, aluminum plate and other plates.

[0031] 2. The primer-free fluororubber coating component of the present invention has excellent resistance to automobile refrigerant and can withstand a 1:1 refrigerant of ethylene glycol and water at 120°C for more than 500 hours; and when the coating is used to prepare metal fluororubber composite plates, fewer coating steps are required, thereby improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a picture of the finished product of the fluororubber primer-free coating obtained by mixing material A and material B in Example 1 of the present invention;

[0033] Figure 2 Is Figure 1 Figure 1. A metal-fluororubber composite panel in which the fluororubber primer-free coating product is applied to a metal plate. DETAILED DESCRIPTION

[0034] The specific implementation modes of the present invention are described in detail below in conjunction with specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.

[0035] Example 1

[0036] A fluororubber primer-free coating resistant to freezing liquid, the fluororubber primer-free coating consisting of material A and material B in a volume ratio of 5:1, wherein, by weight, the material A comprises 50kg of fluororubber, 8kg of carbon black, 5kg of graphite, 5kg of active magnesium oxide, 0.5kg of an adhesive agent and 130kg of butyl acetate; the material B comprises 0.1kg of benzyltriphenylphosphonium chloride, a composite vulcanizing agent (1.5kg of bisphenol AF, 1.5kg of tetrabutylammonium bromide of trithiocyanate) and 52.5kg of methanol, wherein the adhesive agent is a urea-formaldehyde resin adhesive.

[0037] The method for preparing the refrigeration-resistant fluororubber primer-free coating comprises material preparation, ingredient mixing, material A preparation and material B preparation. Specifically, the method comprises the following steps:

[0038] S1, prepare materials:

[0039] The specific steps of preparing active magnesium oxide are as follows: magnesium chloride hexahydrate MgCl2·6H2O and urea CO(NH2)2 are added into a three-necked flask at a ratio of 1:5 to prepare a solution, heated in a water bath to 78°C, stirred to react until a precipitate is produced, 1.4% by mass of polyethylene glycol octylphenyl ether and 0.4% by mass of MnO2 are added, reacted for another 3 hours, naturally cooled and aged for 2 hours, filtered, washed repeatedly with water, and a white precipitate of precursor magnesium hydroxide is obtained; the precursor magnesium hydroxide is then heated at 6°C. The muffle furnace is heated to 725°C at a heating rate of / min, and the temperature is kept at 725°C for calcination for 40min, and then the temperature is lowered to 500-550°C for calcination for 60min to obtain active magnesium oxide, and the obtained active magnesium oxide is sieved to obtain the weight percentage of active magnesium oxide of each particle size: the content of particle size ≤100nm is 13%, the content of particle size 100nm<particle size ≤200nm is 63%, the content of particle size 200nm<particle size ≤250nm is 19%, and the content of particle size 250nm<particle size is 5%;

[0040] The ash content of carbon black is 0.32-0.47% and the average particle size is 100 μm;

[0041] Graphite with an average particle size of 2.5 μm was prepared for later use.

[0042] S2, ingredients: the A material includes 50kg fluororubber, 8kg carbon black, 5kg graphite, 5kg active magnesium oxide, 0.5kg bonding agent and 130kg butyl acetate; the B material includes 0.1kg benzyltriphenylphosphonium chloride, 1.5kg bisphenol AF, 1.5kg tetrabutylammonium bromide trithiocyanate and 52.5kg methanol.

[0043] S3, A material preparation

[0044] After 50 kg of fluororubber is made into small pieces, it is put into a stirring kettle with 130 kg of butyl acetate to stir and dissolve, and then active magnesium oxide, carbon black, graphite and bonding agent are added into the stirring kettle to mix well to prepare pre-treated material A; the pre-treated material A is ground 3-7 times with a sand mill, filtered with a 200-300 mesh filter, and packaged to obtain material A.

[0045] S4, B material preparation

[0046] Weigh benzyl triphenyl phosphonium chloride, bisphenol AF, tetrabutyl ammonium thiocyanate bromide and methanol according to weight proportions; stir, dissolve and mix benzyl triphenyl phosphonium chloride, bisphenol AF, tetrabutyl ammonium thiocyanate bromide and methanol to obtain material B;

[0047] S5, the material A and the material B are uniformly mixed in a volume ratio of 5:1 to prepare a fluororubber primer-free coating.

[0048] A fluororubber primer-free coating resistant to freezing liquid is applied. The material A and the material B prepared above are mixed evenly at a volume ratio of 5:1, and then the mixture is sprayed on a clean metal plate, placed in a blast oven for high-temperature vulcanization at 200°C for 1.8 hours, and a metal fluororubber composite plate is obtained after cooling. The metal fluororubber composite plate is used for the preparation of a cylinder gasket of an automobile internal combustion engine.

[0049] Example 2

[0050] A fluororubber primer-free coating resistant to freezing liquid, the fluororubber primer-free coating consisting of material A and material B in a volume ratio of 5:0.8, wherein the raw materials of material A include 50kg of fluororubber, 10kg of carbon black, 5kg of graphite, 5kg of active magnesium oxide, 0.5kg of an adhesive agent and 130kg of butyl acetate, and the raw materials of material B include 0.1kg of benzyltriphenylphosphonium chloride, a composite vulcanizing agent (2kg of bisphenol AF, 1kg of tetrabutylammonium bromide of trithiocyanate) and 46.5kg of methanol, wherein the adhesive agent is an amino resin adhesive.

[0051] The method for preparing the refrigeration-resistant fluororubber primer-free coating comprises material preparation, ingredient mixing, material A preparation and material B preparation. Specifically, the method comprises the following steps:

[0052] S1, prepare materials:

[0053] The specific steps of preparing active magnesium oxide are as follows: magnesium chloride hexahydrate MgCl2·6H2O and urea CO(NH2)2 are added into a three-necked flask at a ratio of 1:5 to prepare a solution, heated in a water bath to 78°C, stirred to react until a precipitate is produced, 1.4% by mass of polyethylene glycol octylphenyl ether and 0.4% by mass of MnO2 are added, reacted for another 3 hours, naturally cooled and aged for 2 hours, filtered, washed repeatedly with water, and a white precipitate of precursor magnesium hydroxide is obtained; the precursor magnesium hydroxide is then heated at 6°C. The muffle furnace is heated to 725°C at a heating rate of / min, and the temperature is kept at 725°C for calcination for 40min, and then the temperature is lowered to 500-550°C for calcination for 60min to obtain active magnesium oxide, and the obtained active magnesium oxide is sieved to obtain the weight percentage of active magnesium oxide of each particle size: the content of particle size ≤100nm is 8%, the content of particle size 100nm<particle size ≤200nm is 66%, the content of particle size 200nm<particle size ≤250nm is 21%, and the content of particle size 250nm<particle size is 5%;

[0054] The ash content of carbon black is 0.32% and the average particle size is 100 μm;

[0055] Graphite with an average particle size of 2.5 μm was prepared for later use.

[0056] S2, ingredients: 50kg fluororubber, 10kg carbon black, 5kg graphite, 5kg active magnesium oxide, 0.5kg bonding agent, 130kg butyl acetate, 0.1kg benzyltriphenylphosphonium chloride, 2kg bisphenol AF, 1kg tetrabutylammonium bromide trithiocyanate and 46.5kg methanol.

[0057] S3, A material preparation

[0058] After 50 kg of fluororubber is made into small pieces, it is put into a stirring kettle with 130 kg of butyl acetate to stir and dissolve, and then active magnesium oxide, carbon black, graphite and bonding agent are added into the stirring kettle to mix well to prepare pre-treated material A; the pre-treated material A is ground 3-7 times with a sand mill, filtered with a 200-300 mesh filter, and packaged to obtain material A.

[0059] S4, B material preparation

[0060] Weigh benzyl triphenyl phosphonium chloride, bisphenol AF, tetrabutyl ammonium thiocyanate bromide and methanol according to weight proportions; stir, dissolve and mix benzyl triphenyl phosphonium chloride, bisphenol AF, tetrabutyl ammonium thiocyanate bromide and methanol to obtain material B;

[0061] S5, the material A and the material B are uniformly mixed in a volume ratio of 5:0.8 to prepare a fluororubber primer-free coating.

[0062] A fluororubber primer-free coating resistant to freezing liquid is applied. The material A and the material B prepared above are mixed evenly in a volume ratio of 5:0.8, applied to a cleaned metal plate by flow coating, placed in a blast oven for high-temperature vulcanization at 200°C for 1.3 hours, and after cooling, a metal fluororubber composite plate is obtained. The metal fluororubber composite plate is used for the preparation of a cylinder gasket of an automobile internal combustion engine.

[0063] Example 3

[0064] A fluororubber primer-free coating resistant to freezing liquid, the fluororubber primer-free coating consisting of material A and material B in a volume ratio of 5:1.2, wherein the raw materials of material A include 50kg of fluororubber, 10kg of carbon black, 5kg of graphite, 5kg of active magnesium oxide, 0.5kg of an adhesive agent and 130kg of butyl acetate, and the raw materials of material B include 0.1kg of benzyltriphenylphosphonium chloride, a composite vulcanizing agent (2kg of bisphenol AF, 1kg of tetrabutylammonium bromide of trithiocyanate) and 46.5kg of methanol, wherein the adhesive agent is an amino resin adhesive.

[0065] The method for preparing the refrigeration-resistant fluororubber primer-free coating comprises material preparation, ingredient mixing, material A preparation and material B preparation. Specifically, the method comprises the following steps:

[0066] S1, prepare materials:

[0067] The specific steps of preparing active magnesium oxide are as follows: magnesium chloride hexahydrate MgCl2·6H2O and urea CO(NH2)2 are added into a three-necked flask at a ratio of 1:5 to prepare a solution, heated in a water bath to 78°C, stirred to react until a precipitate is produced, 1.4% by mass of polyethylene glycol octylphenyl ether and 0.4% by mass of MnO2 are added, reacted for another 3 hours, naturally cooled and aged for 2 hours, filtered, washed repeatedly with water, and a white precipitate of precursor magnesium hydroxide is obtained; the precursor magnesium hydroxide is then heated at 6°C. The muffle furnace is heated to 725°C at a heating rate of / min, and the temperature is kept at 725°C for calcination for 40min, and then the temperature is lowered to 500-550°C for calcination for 60min to obtain active magnesium oxide, and the obtained active magnesium oxide is sieved to obtain the weight percentage of active magnesium oxide of each particle size: the content of particle size ≤100nm is 11%, the content of particle size 100nm<particle size ≤200nm is 64%, the content of particle size 200nm<particle size ≤250nm is 17%, and the content of particle size 250nm<particle size is 8%;

[0068] The ash content of carbon black is 0.32-0.47% and the average particle size is 100 μm;

[0069] Graphite with an average particle size of 2.5 μm was prepared for later use.

[0070] S2, ingredients: the A material includes 50kg fluororubber, 8kg carbon black, 5kg graphite, 5kg active magnesium oxide, 0.5kg bonding agent and 130kg butyl acetate; the B material includes 0.1kg benzyltriphenylphosphonium chloride, 1.5kg bisphenol AF, 1.5kg tetrabutylammonium bromide trithiocyanate and 52.5kg methanol.

[0071] S3, A material preparation

[0072] After 50 kg of fluororubber is made into small pieces, it is put into a stirring kettle with 130 kg of butyl acetate to stir and dissolve, and then active magnesium oxide, carbon black, graphite and bonding agent are added into the stirring kettle to mix well to prepare pre-treated material A; the pre-treated material A is ground 3-7 times with a sand mill, filtered with a 200-300 mesh filter, and packaged to obtain material A.

[0073] S4, B material preparation

[0074] Weigh benzyl triphenyl phosphonium chloride, bisphenol AF, tetrabutyl ammonium thiocyanate bromide and methanol according to weight proportions; stir, dissolve and mix benzyl triphenyl phosphonium chloride, bisphenol AF, tetrabutyl ammonium thiocyanate bromide and methanol to obtain material B;

[0075] S5, the material A and the material B are uniformly mixed in a volume ratio of 5:1.2 to prepare a fluororubber primer-free coating.

[0076] A fluororubber primer-free coating resistant to freezing liquid is applied. The A material and the B material prepared above are mixed evenly in a volume ratio of 5:1.2, and then coated on a clean metal plate by roller coating. The metal plate is placed in a blast oven for high-temperature vulcanization at 200°C for 1.5 hours, and a metal fluororubber composite plate is obtained after cooling. The metal fluororubber composite plate is used for the preparation of a cylinder gasket of an automobile internal combustion engine.

[0077] Comparative Example 1

[0078] It is basically the same as Example 1, except that the active magnesium oxide in the material A is replaced by magnesium oxide with an average particle size of 6.5 μm.

[0079] Comparative Example 2

[0080] It is basically the same as Example 1, except that the material A includes 50kg fluororubber, 8kg carbon black, 5kg graphite, 0.5kg bonding agent and 130kg butyl acetate; the material B includes 0.1kg benzyltriphenylphosphonium chloride, a composite vulcanizing agent of 1.5kg bisphenol AF and 52.5kg methanol, wherein the bonding agent is a urea-formaldehyde resin adhesive.

[0081] Comparative Example 3

[0082] It is basically the same as Example 1, except that the preparation method of active magnesium oxide is different.

[0083] The method for preparing the refrigeration-resistant fluororubber primer-free coating comprises material preparation, ingredient mixing, material A preparation and material B preparation. Specifically, the method comprises the following steps:

[0084] S1, prepare materials:

[0085] The specific steps of preparing active magnesium oxide are as follows: adding magnesium chloride hexahydrate MgCl2·6H2O and urea CO(NH2)2 in a ratio of 1:5 into a three-necked flask to prepare a solution, heating to 99°C in a water bath, stirring to react until precipitation is generated, adding 2% polyethylene glycol octylphenyl ether by mass, reacting for another 3 hours, cooling naturally and aging for 1 hour, filtering, and repeatedly washing with water to obtain a white precipitate of precursor magnesium hydroxide; then placing the precursor magnesium hydroxide in a muffle furnace and heating it to 500°C and calcining it for 120 minutes to obtain active magnesium oxide, and sieving the obtained active magnesium oxide to obtain the weight percentage of active magnesium oxide of each particle size: 48% for particles with a particle size of 200nm<particle size≤250nm, and 52% for particles with a particle size of 250nm<particle size.

[0086] Comparative Example 4

[0087] The method is basically the same as Example 1, except that fumed silica with an average particle size of 58 μm replaces graphite, and the bonding agent is methyltrimethoxysilane.

[0088] The coating performance test in the above coating specific embodiment, the method of the performance test and the observation method thereof are as follows:

[0089] Solid content determination test: GB / T 6740-86 Determination of volatile and non-volatile matter in paints;

[0090] Appearance after coating: The prepared metal fluororubber composite plate coated with fluororubber primer-free coating was placed under an observation lamp and three observers observed and evaluated the appearance of the coated surface.

[0091] Table 1 The solid content, viscosity, fluidity and other properties of the coating in each specific embodiment

[0092] Group Solid content (%) Viscosity (mPa.s) Appearance after coating Example 1 35%±2% 2500-3500 Smooth and bright Example 2 35%±2% 2500-3500 Smooth and bright Example 3 35%±2% 2500-3500 Smooth and bright Comparative Example 1 38%±2% 2000-3000 Rough paint surface Comparative Example 2 32%±3% 2500-3500 Smooth and bright Comparative Example 3 35%±2% 2500-3500 Smooth and bright Comparative Example 4 35%±2% 2500-3500 Rough paint surface

[0093] It can be seen from Table 1 above that, compared with the coating of Comparative Example 1, although the solid content of Example 1 using the method of the present invention is less than that of Comparative Example 1, since ordinary magnesium oxide is used in Comparative Example 1, the magnesium oxide has a large particle size and no unsaturated valence bonds inside for combining with other components in the coating, a tight structure cannot be formed between the components, resulting in a decrease in the overall viscosity of the coating; compared with Comparative Examples 2 and 3, the performance of the coating of Example 1 using the method of the present invention is not much different; compared with Comparative Example 4, the graphite in the coating of Example 1 using the method of the present invention has the effect of improving the dispersibility of the coating, reducing the agglomeration of components, and improving the uniformity of coating coating and the smoothness of the coating surface.

[0094] The coatings of each specific embodiment were used to prepare composite boards, and the appearance, crush resistance, oil resistance, heat resistance and freezing liquid resistance of the composite boards were tested. The results are shown in Table 2. The specific measurement methods are as follows:

[0095] 1. Anti-crush test: Under the test conditions of torque 28N·m×230℃×1h, observe the crush area of ​​the composite plate;

[0096] 2. Oil resistance test: Soak the composite board in 170℃ gasoline engine oil 10W / 30 for 72 hours, and observe whether the coating layer of the composite board has bulging, blistering, or shedding;

[0097] 3. 250℃×12h heat resistance test: After using the GB / T 3512-2014 test method, observe whether the coating layer of the composite board has bulging, blistering, or shedding;

[0098] 3. Freezing liquid resistance test: After the composite board to be tested is immersed in 120℃ freezing liquid (ethylene glycol and water 1:1) for 500 hours, observe whether the coating layer of the composite board has bulging, blistering, or shedding.

[0099] Table 2

[0100]

[0101]

[0102] As can be seen from Table 2, the fluororubber primer-free coating prepared by the method embodiment of the present invention is compared with the coatings of Comparative Examples 1 and 3. The chemical properties and physical properties of the activated magnesium oxide of different particle sizes prepared by the method of the present invention are good. The activated magnesium oxide of different particle sizes is mixed with fluororubber, carbon black and graphite, and dispersed and filled between the fluororubber, carbon black and graphite during coating, thereby increasing the effective supporting surface and thus enhancing the crush resistance. At the same time, the activated magnesium oxide prepared by the method of the present invention has high activity, and there are many unsaturated valence bonds on its surface, which are easy for other molecules to combine into a stable structure, thereby improving the heat resistance of the coating, and at the same time increasing the tightness between the components in the coating, thereby improving the coating. The invention discloses a novel coating composition comprising a triazine trithiol compound and a fluororubber compound. The coating composition comprises a triazine trithiol compound and a fluororubber compound. The triazine trithiol compound comprises a fluororubber compound and a fluororubber compound. The fluororubber ...

[0103] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A fluororubber primer-free coating resistant to freezing liquid, characterized in that: The fluororubber primer-free coating is composed of material A and material B in a volume ratio of 5:0.8-1.2, wherein the raw materials of material A include 40-60 parts of fluororubber, 5-8 parts of active magnesium oxide, 5-10 parts of carbon black, 5-10 parts of graphite, 2-4 parts of bonding aid and 100-200 parts of solvent; the raw materials of material B include 1-1.5 parts of accelerator, 1.5-3 parts of composite vulcanizing agent and 40-100 parts of solvent, wherein the composite vulcanizing agent includes one or two of triazine trithiol compounds and bisphenol AF, the accelerator is benzyl triphenyl phosphonium chloride, and the bonding aid is an amino compound. The preparation method of the active magnesium oxide is as follows: the magnesium hydroxide is heated to 700-750°C in a muffle furnace at a heating rate of 6-10°C / min, the temperature is kept at calcination for 30-50 min, and then the temperature is reduced to 500-550°C and the temperature is kept at calcination for 40-70 min to obtain the active magnesium oxide.

2. The fluorine rubber primer-free coating resistant to freezing liquid according to claim 1, characterized in that: The active magnesium oxide is composed of four particle sizes of active magnesium oxide. In terms of weight percentage, the proportions of the four particle sizes of active magnesium oxide are as follows: 5-15% of the particle size ≤100 nm, 60-70% of the particle size 100 nm<particle size ≤200 nm, 15-25% of the particle size 200 nm<particle size ≤250 nm, and 4-10% of the particle size 250 nm<particle size.

3. A method for preparing a fluororubber primer-free coating resistant to freezing liquid as claimed in any one of claims 1 to 2, characterized in that: The preparation method includes material preparation, batching, preparation of material A and preparation of material B, and the specific method is as follows: S1, preparation: preparing activated magnesium oxide and carbon black; S2, ingredients: by weight, take 40-60 parts of fluororubber, 5-8 parts of active magnesium oxide, 5-10 parts of carbon black, 5-10 parts of graphite, 1-1.5 parts of accelerator, 1.5-3 parts of composite vulcanizing agent, 2-4 parts of bonding agent and 200-300 parts of solvent; S3, preparation of material A: taking the fluororubber, carbon black, graphite, adhesive additive and a preset amount of solvent into a stirring kettle and mixing them evenly to prepare pre-treated material A, grinding the pre-treated material A, filtering and packaging to prepare material A; S4, preparation of material B: taking the accelerator, the composite vulcanizing agent, and a preset amount of solvent and placing them in a stirring kettle, stirring and dissolving and mixing, to obtain material B; S5, the material A and the material B are uniformly mixed in a volume ratio of 5:0.8-1.2 to prepare a fluororubber primer-free coating.

4. The method for preparing the refrigeration-resistant fluororubber primer-free coating according to claim 3, characterized in that: In the step S1, the ash content of the carbon black is 0.32-0.47%, and the average particle size is 100 μm.

5. The method for preparing the fluorine rubber primer-free coating resistant to freezing liquid according to claim 3, characterized in that: In step S1, the specific steps of preparing active magnesium oxide are as follows: (1) Preparation of precursor magnesium hydroxide: magnesium chloride hexahydrate and urea are prepared into a solution in a preset ratio, the water is heated to precipitation, a dispersant is added to react for 3-6 hours, the temperature is naturally lowered and aged for 1 hour, filtered, washed, and a white precipitate is obtained to obtain the precursor magnesium hydroxide; (2) Preparation of active magnesium oxide: The precursor magnesium hydroxide is heated in a muffle furnace to 700-750°C at a heating rate of 6-10°C / min, kept at this temperature for calcination for 30-50 min, and then cooled to 500-550°C and kept at this temperature for calcination for 40-70 min to obtain active magnesium oxide, wherein, by weight percentage, the proportions of four particle sizes of active magnesium oxide are as follows: the content of particle size ≤100 nm is 5-15%, the content of particle size 100nm<particle size ≤200 nm is 60-70%, the content of particle size 200 nm<particle size ≤250 nm is 15-25%, and the content of particle size 250 nm<particle size is 10-20%.

6. The method for preparing the refrigeration-resistant fluororubber primer-free coating according to claim 5, characterized in that: The dispersant is 1.4% by mass of polyethylene glycol octylphenyl ether and 0.4% by mass of MnO2.

7. An application of a fluororubber primer-free coating resistant to freezing liquid, characterized in that: After mixing material A and material B in the freeze-resistant fluororubber primer-free coating as described in any one of claims 1-2 at a ratio of 5:0.8-1.2, the material is applied to a clean metal plate by roller coating, spray coating, flow coating or dipping, and the composite plate is obtained by high-temperature vulcanization for preparing a cylinder gasket of an automobile internal combustion engine.

Citation Information

Patent Citations

  • Preparation method of metal-fluororubber composite sealing plate

    CN102756528B

  • Preparation method of metal affinity vulcanized fluororubber

    CN113121849A

  • Coating solution and fluoro rubber metal layered plate using same

    WO2021070521A1